BIOESTRATIGRAFÍA DEL CARBONÍFERO MARINO DEL VALLE DE CALINGASTA-USPALLATA, PROVINCIAS DE SAN JUAN Y MENDOZA (Ameghiniana, 2014)
A new stratigraphic interpretation of marine Carboniferous deposits of Calingasta-Uspallata valley is given. The Pituil Formation (Amos and Rolleri; emend. nov.), is restricted to Barreal hills outcrops including Tres Saltos, Esquina Gris, Mono Verde and El Retamo units of Mésigos. The San Eduardo Formation (Mésigos; emend. nov.), with El Paso and Hoyada Verde Members is recognized; while its relationships with La Capilla, Leoncito, Yalguaraz, Ansilta and Majaditas Formations are explained. The most important stratigraphic and palaeoenvironmental features of these lithostratigraphic units are given. New biostratigraphic information related to Rugosochonetes-Bulahdelia and Levipustula biozones is given; and a new unit: the Balakhonia-Geniculifera local zone is proposed. The following species are described: Balakhonia peregrina sp. nov., Genicullfera tenuiscostata sp. nov., Neochonetes granulifer (Owen) (brachiopods), Ptychomphalina sabattinii sp. nov., Ptychomphalina turgentis sp. nov., Ptychomphalina cf. kuttungensis (Campbell), Peruvispira reedi Sabattini, Lunulazona sp. nov.?, Auryptigma sp. (gastropods), Aviculopecten barrealensis Reed (bivalve) and Sphenotallus stubblefieldi Schmidt and Teichmüller (annelid"). Levipustula levis Maxwell and Ptychomphalina australis (Sabattini and Noirat) from the San Eduardo Formation (Hoyada Verde Member) are figured.